Prevalence and predictive factors for vitamin D deficiency in pregnant Lebanese women: a retrospective cohort study - Muhieddine Seoud; Iman Jaafar; Dalal Kojok; Sara Sleiman; Talal Seoud; Ghina Ghaziri; Fadi Mirza (Gynecological Endocrinology, 2025)
Objective This study aimed to determine the prevalence of vitamin D deficiency and its associated factors among women attending women’s health clinics at a university medical center in Lebanon.Methods We retrospectively reviewed clinical and obstetric data, including 25-hydroxyvitamin D [25OHD] serum levels and vitamin D3 supplementation, from 873 healthy singleton pregnancies delivered between 2006 and 2017. Women with preexisting comorbidities or prior gestational complications were excluded. VDD was defined as a 25OHD serum level <20 ng/ml.Results At baseline, 63% of participants were vitamin D deficient. Poisson regression was used to identify independent predictors of deficiency. In early gestation, 25OHD levels varied significantly by age, pre-pregnancy BMI, parity, smoking status, and season of presentation (all p < 0.05). At late gestation, vitamin D levels were associated with pre-pregnancy BMI, hemoglobin status at delivery, and vitamin D status at early gestation. Women with 25OHD <20 ng/ml at late gestation were more likely to be anemic compared to those with levels ≥20 ng/ml (adjusted odds ratio 1.6; 95% CI: 1.1–2.5).Conclusion Vitamin D deficiency is highly prevalent among pregnant Lebanese women. Identified risk factors including higher BMI, younger age, multiparity, and anemia should prompt consideration of more aggressive vitamin D supplementation strategies for women planning pregnancy.Synopsis Vitamin D deficiency is quite prevalent among pregnant women in the Middle East. We aim to report the prevalence of Vitamin D deficiency and its associated predictors during pregnancy.